2020
DOI: 10.1186/s40657-020-00210-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and population differences in migration of Whimbrels in the East Asian–Australasian Flyway

Abstract: Background: Conserving migratory birds is challenging due to their reliance on multiple distant sites at different stages of their annual life cycle. The concept of "flyway", which refers to all areas covered by the breeding, nonbreeding, and migrating of birds, provides a framework for international cooperation for conservation. In the same flyway, however, the migratory activities of the same species can differ substantially between seasons and populations. Clarifying the seasonal and population differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…Travel durations of the migrations were also 2–4 times shorter for Whimbrels in these two Atlantic populations than those in our study. Whimbrels using the East Asian–Australasian Flyway (Kuang et al 2020), however, have migratory patterns more similar to those in our study. Whimbrels migrating between two non‐breeding locations in Australia and breeding sites across high‐latitude areas of Asia moved over periods of similar durations to those conducted by Alaska‐breeding Whimbrels, but migrations entailed fewer stops (four and three stops during southbound and northbound migration, respectively; Kuang et al 2020) than migrations by Alaska‐breeding Whimbrels in our study.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Travel durations of the migrations were also 2–4 times shorter for Whimbrels in these two Atlantic populations than those in our study. Whimbrels using the East Asian–Australasian Flyway (Kuang et al 2020), however, have migratory patterns more similar to those in our study. Whimbrels migrating between two non‐breeding locations in Australia and breeding sites across high‐latitude areas of Asia moved over periods of similar durations to those conducted by Alaska‐breeding Whimbrels, but migrations entailed fewer stops (four and three stops during southbound and northbound migration, respectively; Kuang et al 2020) than migrations by Alaska‐breeding Whimbrels in our study.…”
Section: Discussionsupporting
confidence: 77%
“…Whimbrels at southerly non‐breeding sites also began northbound migration earlier than those at more northerly locations. In contrast, Kuang et al (2020) found little variation in the timing or duration of migratory movements of Whimbrels in the East Asian–Australasian Flyway, possibly due to the relatively restricted ranges of breeding (~ 10°) and non‐breeding (~ 5°) latitudes of birds in their study. Similarly, Johnson et al (2016) and Carneiro et al (2019a,b, 2020) monitored Whimbrels in the Atlantic Flyway from one breeding site each across non‐breeding latitudes that were relatively restricted (~ 10° in both studies) compared to those in our study.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…1 , Supplementary Table S1 ). Most Whimbrels that we tracked from Singapore took a similar route to birds from Australia that migrated through coastal east China to breed in the Russian Far East 24 , 39 . The Whimbrel that crossed the Himalayas probably represents a different breeding population than those migrating along the EAAF, whereas for Common Redshanks, those crossing the Himalayas tended to be the more westerly breeders within one population.…”
Section: Discussionmentioning
confidence: 99%